PRIVACY PRESERVING ADVANCED SECURITY ON UNTRUSTED CLOUD WITH SELF BACKUP PROCESS - Abdulameer, Sadeer Dheyaa (International Journal of Research -GRANTHAALAYAH, 2017)
Cloud Storage service are frequently required for many corporate and government organizations. Most of cloud storage service providers are un-trusted, so it is not safe to keep the data in cloud for long period. Many are using cloud storage for data sharing that means it is not possible to send a big file in email, maximum 25 GB are allowed, for big files, files are uploaded in cloud storage and link is given to the data consumer. After Data consumer download the file, Data owner has to delete the file from the cloud for the security reasons, but most of time Data Owner forget to delete the file. To overcome this problem data self-destruction is proposed in many papers and now proposed system has Self-Destruction cum Self-Backup Process, which help the file to stay in the public cloud for certain period of times and it will be removed from the cloud storage and securely stored in another storage. To verify the integrity of the file HMAC is created while file is uploaded and Data Consumer can able to download the file and generate the HMAC, check the integrity of the file.